Arterial Thrombotic Events in Hospitalized COVID-19 Patients: A Short Review and Meta-Analysis - Candeloro, Matteo; Schulman, Sam (Seminars in Thrombosis and Hemostasis, 2022)
It is well established that the risk of venous thromboembolism is high in coronavirus disease 19 (COVID-19). The frequency of arterial thromboembolic events (ATEs) in hospitalized patients with COVID-19 is unclear, as is the magnitude of these events in comparison with other infections. We searched MEDLINE from February 2020 to February 2022 for prospective or retrospective cohort studies and randomized clinical trials that reported the number of acute myocardial infarction (AMI), acute ischemic stroke (AIS), acute limb ischemia (ALI), or other ATE as defined by the original authors in hospitalized patients with COVID-19. The pooled frequencies were calculated through meta-analysis using random effects model with logit transformation and presented with relative 95% prediction intervals (95% PI). We retrieved a total of 4,547 studies, 36 of which (28 retrospective cohorts, five prospective cohorts and three randomized trials) were finally included in our analysis. The resulting cohort counted 100,949 patients, 2,641 (2.6%) of whom experienced ATE. The pooled ATE frequency was 2.0% (95% PI, 0.4–9.6%). The pooled ATE frequency for AMI, AIS, ALI, and other ATE was 0.8% (95% PI, 0.1–8.1%), 0.9% (95% PI, 0.3–2.9%), 0.2% (95% PI, 0.0–4.2%), and 0.5% (95% PI, 0.1–3.0%), respectively. In comparison with the ATE incidence reported in three studies on non-COVID viral pneumonia, we did not detect a significant difference from the results in our analysis. In conclusion, we found a non-negligible proportion of ATE in patients hospitalized for COVID-19. Our results are similar to those found in hospitalized patients with influenza or with non-COVID viral pneumonia.
Keywords: COVID-19; stroke; myocardial infarction; ischemia; thromboembolism